Understanding Parental Role in Children’s Participation In Decision-Making During Hospitalization: An Ethnographic Study In Malaysia - Lee, Siew Pien; Haycock-Stuart, Elaine; Ashikin, Atan; Rpzita, Noodin (2023)
Background: It has been acknowledged globally that children have the right to participate in affairs that impact their lives. This has led to more initiatives to promote and support children’s participation in health care, however, there remains a lack of studies in this area, particularly in Malaysia. The aim was to explore children’s experiences of participation in communication exchanges and decision-making concerning nursing care in a paediatrics setting in Malaysia. Methods: This study adopted a focused ethnography design within a constructivist research paradigm. Participant observations and semi-structured interviews were conducted with 21 children, 21 parents, and 19 nurses at a paediatric ward in Malaysia. All observation field notes, and interview recordings were transcribed verbatim. A focused ethnographic data analysis technique was performed to analyze the data. Results: Three themes emerged from the situations where children participated in communication exchanges and decision-making in an oncology setting: (i) children being excluded, (ii) children’s expressions being ignored, (iii) children being consulted, (iv) shifting degrees of participation. Conclusion: Although children want to be included in the communication exchange and decision-making process, they have a marginal role, which indicates the need for clear guidelines or policies that reflect all stakeholder views. Children should be supported in having their voices heard in matters that affect them.